(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2024)
Safety focuses not only on the effectiveness of treatment, but also on trust in the procedures and integrity of the system of care. This article corresponds to a result of the research project “Promotion strategies on adherence to pharmacological treatment in patients at the León Becerra Hospital in Guayaquil” developed by teachers and students of the Pharmacy Assistance career, of the TES. The objective sought is to analyze how the safety culture allows guaranteeing quality in medical care at the León Becerra Hospital in Guayaquil, an explanatory investigation was used, for the study sample five documentary theses were analyzed, which allowed an in-depth analysis of the topic, the techniques were the documentary review and longitudinal study technique, as an instrument the results collection sheet was applied.